Logistic regression approach in studying travel demand during morning peak hour: A case study in Klang Komuter Station, Malaysia - Mohd Ali, Nur Fahriza; Mohd Sadullah, Ahmad Farhan; Zulkiple, A. (Penerbit UMP, 2022)
This paper develops a Stated Preference (SP) experiment that provides a way to measure users’ travel demand in public transport. This paper introduces an empirical procedure for optimising the SP experiment. This procedure permits the identification of the choice alternatives defining the experiment by simulating the choices of a user sample. By using the data collected from a survey, a Logit model was calibrated. This model is a way of identifying the importance of service quality attributes on global users’ satisfaction which provides an operationally appealing measure of current or potential service effectiveness. The result shows that out-ofvehicle time gives a great impact towards users’ mode choice